Особливості будови мікроциркуляторного русла м’яких тканин пародонту при використанні різних пломбувальних матеріалів на тлі експериментального цукрового діабету в динаміці - Варакута, Ольга Анатоліївна; Кущ, Оксана Георгіївна; Варакута, О. А.; Кущ, О. Г.; Varakyta, O. A.; Kushch, O. G. (Полтава : Українська медична стоматологічна академія, 2016)
Встановлено суттєве зростання частоти розвитку алергонепереносимості різних стомато¬логічних матеріалів. Бісфенол А, що входить до складу фотополімерної пломби впливає на органи і систе¬ми, чутливі до естрогену, а – метакрилат залишається неполімералізованим після фотополімерізації, що представляє токсикологічну загрозу для пацієнта, включаючи алергічний контактний стоматит. Особливо погіршується ситуація, якщо стоматологічний пацієнт страждає на цукровий діабет. Тому, було досліджено як змінюється структура мікроциркуляторного русла в пародонті у щурів при наявності пломбувального матеріалу на тлі цукрового діабету. За умов стрептозотоцин-індукованого цукрового діабету виникають і поступово прогресують структурні перебудови мікроциркуляторного русла у м’яких тканинах пародонта. При наявності пломбувального матеріалу на тлі цукрового діабету одночасно з перебудовою мікроцир¬куляторного русла збільшується кількість лімфоцитів у власній пластинці і кількість тучних клітин навколо ясневого карману. Установлен существенный рост частоты развития аллергий на различные стоматологические материалы. Бисфенол А, который входит в состав фотополимерной пломбы влияет на органы и системы, чувствительные к эстрогену, а – метакрилат оставшийся неполимерализованым после фотополимериза¬ции, представляет токсикологическую опасность для пациента, включая аллергический контактный сто¬матит. Особенно ухудшается ситуация, если стоматологический пациент страдает сахарным диабетом. Поэтому, было исследовано как изменяется структура микроциркуляторного русла в пародонте у крыс при наличии пломбы на фоне сахарного диабета. В условиях стрептозотоцин-индуцированного сахар¬ного диабета возникают и постепенно прогрессируют структурные перестройки микроциркуляторного русла в мягких тканях пародонта. При наличии пломбировочного материала на фоне сахарного диабе¬та одновременно с перестройкой микроциркуляторного русла увеличивается количество лимфоцитов в собственной пластинке и количество тучных клеток вокруг десневого кармана. Established substantial increase in the incidence of allergy intolerance of different dental materi¬als, as manifested by specific T-cell responses of the body, mainly psevdoalerhichnymy or a combination thereof. However, dentist, choosing materials for preventive measures and restoration of teeth guided by several cri¬teria, including: aesthetics, duration of therapy guarantees, comfort in work and price / quality ratio. Such re¬quirements fully in the present, corresponds plastic composite light curing renhenkontrasnyy GC Gradia Direct Flo (Japan), which includes traditional resin – dymetylakrylat – BisGMA. Bisphenol A, which is part of the photo¬polymer fillings affects the organs and systems that are sensitive to estrogen, and – the remaining methacrylate without polymerization after photopolymerization, is toxicological danger to the patient, including allergic contact stomatitis. Especially the situation worsens if the dental patient suffers from diabetes. Therefore, it was investi¬gated how the microvasculature structure periodontitis in rats in the presence of the seals and diabetes mellitus. The structure of periodontal tissue in rats with induced diabetes in dynamics, and when combined with the presence of this pathology photopolymer and cement fillings. Under the conditions of streptozotocin-induced diabetes occur gradually and are progressing structural changes of the microvasculature in the soft periodontal tissues. Arteriolar lumen narrowing. The walls of capillaries and arterioles will melt fat some, especially in the papillary layer. Connective tissue papillae are smoother appearance. Intraepithelial, subepithelial, in the area marked gingival crevices different infiltration, indicating acute inflammation. Small hemorrhages are marked. In the lamina propria mucosa lumen vascular microcirculation narrowed. Was marked venous plethora, dilatation lumen of the capillaries. In papillary layer arteriolar lumen is 10,9 ± 0,09 mкm, the capillaries – 6,6 ± 0,33 mкm, and venules – 21 ± 0,014 mкm. In papillary layer around blood vessels were found lymphocytes, macrophages and mast cells. In the reticular layer, visually increasing the number of macrophages and mast cells. In the presence of photopolymer filling material diabetes mellitus along with the restructuring of the micro¬vasculature increases the number of lymphocytes in the lamina propria and the number of fat cells around the gingival pocket. In animals in which the filling material was presented against the background of a cement material diabetes changes concerning the restructuring of the microvasculature, for animals with diabetes.
Особенности строения микроциркуляторного русла мягких тканей пародонта при использовании разных пломбировочных материалов на фоне экспериментального сахарного диабета в динамике
Avilable microvasculature soft periodontal tissues using different filling materi-als on the background of experimental diabetes in dynamiсs
Keywords: стрептозотоцин-індукований цукровий діабет; пломба; мікроциркуляторне русло; стрептозотоцин-индуцированный сахарный диабет; микроциркуляторное русло; streptozotocin-induced diabetes; seal; microcirculatory bed